2013
DOI: 10.1002/ccd.24896
|View full text |Cite
|
Sign up to set email alerts
|

Transradial intervention for patients with ST elevation myocardial infarction with or without cardiogenic shock

Abstract: In TRI high volume center, TRI for STEMI was safe and feasible as a default approach. TRI could be applied to severe shock patients with similar clinical outcome to TFI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
5
1
Order By: Relevance
“…This is probably a consequence of their definition of CS, with a blood pressure threshold <100 mmHg rather than the <90 mmHg usually used in other studies. Our procedural success rate of 70.3% is broadly similar to previous series in CS [13,14,16], with the exception of one study that reported an impressive success rate of 95.3% [15].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This is probably a consequence of their definition of CS, with a blood pressure threshold <100 mmHg rather than the <90 mmHg usually used in other studies. Our procedural success rate of 70.3% is broadly similar to previous series in CS [13,14,16], with the exception of one study that reported an impressive success rate of 95.3% [15].…”
Section: Discussionsupporting
confidence: 90%
“…This may be explained by the 70% radial access rate and the use of smaller diameter sheaths (5F and 6F) in our centre. Two other studies reported a lower rate of major bleeding [14,16]. However, under-reporting of bleeding complications is a common bias: outcome data were not available for 10% of the cohort in one study [16], and no precise definition of bleeding was provided in another study [14].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations